RETENSI BAHAN PENGAWET CAMPURAN BORAKS DAN ASAM BORAT MENGGUNAKAN METODE RENDAMAN DINGIN PADA BILAH BAMBU SERO (Schizostachyum brachycladum Kurz) MENURUT ARAH PANJANG BATANG - Samal, Muhammad Miraz; Liliefna, Leonard Dantje; Tan, Lieke (MARSEGU : Jurnal Sains dan Teknologi, 2024)
The objectives of this study were to determine the retention of a mixture of borax and boric acid solution at a concentration of 6% with a ratio of borax:boric acid = 2:1 on sero bamboo strips soaked for 72 hours, and to analyze the effect of position along the bamboo culm on the retention of preservatives. This study was designed using a factorial experiment on randomized block design with one factor, namely position along the culm with six treatment levels of 0, 20, 40, 60, 80, and 100%, and with four bamboo culms as groups. The response variables observed included air dry moisture content and retention of preservatives into the bamboo strips. The results showed that the moisture content was evenly distributed among all test samples and the preservative retention level was between 16.8 - 26.9 kg/m3 with an average value of 22 kg/m3, while the position along the bamboo culm had no effect on preservative retention.